2012
DOI: 10.1111/j.1365-2427.2012.02846.x
|View full text |Cite
|
Sign up to set email alerts
|

Disease and pollution alter Daphnia taxonomic and clonal structure in experimental assemblages

Abstract: Summary 1. Environmental stressors can influence population and community structure. However, the majority of experimental work on multiple environmental stressors has been done at the individual level only. 2. In this work, we followed changes in experimental assemblages of Daphnia (waterfleas; consisting of two taxa and three clones per taxon) after exposure to the fungal parasite Metschnikowia sp. and/or the pesticide diazinon. 3. We found a significant shift in taxonomic and clonal composition under both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…We specifically hypothesized that DPH would confer a protective effect for DZN poisoning in aquatic invertebrates and vertebrates. Threshold toxicity values observed here for Daphnia magna to DZN generally followed previous reports for both acute (40)(41)(42) and subchronic (42,43) endpoints. Though DPH and other antihistamine toxicity data for invertebrates is not as readily available as DZN (44), Daphnia magna observations from the present study are similar to previous reports by our group (26) and others (45).…”
Section: Discussionsupporting
confidence: 88%
“…We specifically hypothesized that DPH would confer a protective effect for DZN poisoning in aquatic invertebrates and vertebrates. Threshold toxicity values observed here for Daphnia magna to DZN generally followed previous reports for both acute (40)(41)(42) and subchronic (42,43) endpoints. Though DPH and other antihistamine toxicity data for invertebrates is not as readily available as DZN (44), Daphnia magna observations from the present study are similar to previous reports by our group (26) and others (45).…”
Section: Discussionsupporting
confidence: 88%
“…Interaction between these stressors can exacerbate or mitigate their otherwise independent effects [ 29 ]. This study was motivated by the need for a clarification on how pesticide pollution affects the eventual spread of diseases [ 23 , 42 ]. Our major finding was that two common agrochemicals (fungicides) cause different outcomes in a host-parasite ( Daphnia - M .…”
Section: Discussionmentioning
confidence: 99%
“…galeata ; hereafter designated as clone 12 and clone 47, respectively) were selected as model hosts, and maintained as single-cohort group cultures in the laboratory. These Daphnia genotypes were isolated from Lake Ammersee (Germany), and they are part of a collection of Daphnia clones that have been used in other studies [ 23 , 34 ]. The use of more than one genotype/taxon increases ecological relevance, but the use of numerous clones is often not logistically feasible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Offspring from a highest level of mixed pollutants showed a higher mortality rate than other groups but produced as many neonates per clutch as the control, which suggested that energy allocated to maintain production was not reduced although the shortened lifespan meant cost of fitness (Buser et al 2012). Offspring from other lower levels of mixed or single pollutants showed no significant difference in survival or development, and no mortality was observed before maturation in our experiments, indicating that the offspring was not severely affected.…”
Section: Discussionmentioning
confidence: 80%